The Relationship of Risk Factors With The Incidence Of Postoperative Nausea And Vomiting In Patients who underwent surgery with General Anesthesia at Rsi Siti Rahmah - Anita Darmayanti; Oka Yughana; Bun Yurizali (Science Midwifery, 2022)
General anesthesia is a medical procedure that aims to relieve pain, lose consciousness, and be predictable. General anesthesia has side effects in the form of PONV which cancause dehydration, electrolyte imbalance, re-open wounds, pulmonary aspiration and delay in discharge from the hospital. To know the characteristics of general anesthesia patients, to know the degree of PONV, and to know the relationship between patient, intraoperative, and postoperative risk factors who experience PONV in patients undergoing surgery under anesthesia general.The type of this research used is analytic observational with a cross-sectional approach. The affordable population in this study were all general anesthesia patients at Siti Rahmah Hospital Padang with 65 samples using a consecutive sampling technique. Analysis of univariate and bivariate data presented in the form of frequency and percentage distributions, data processing using the Kolgomorov Smirnov test statistical test. General anesthesia patients aged 26-35 years (24.6%), female (56.9%), no smoking history (89.2%), surgical oncology (47.7%), 60 minutes duration (67.7%), mild pain (38.5%), opioid use (92.3%). Grade 0 PONV (87.6%). The relationship of risk factors for patients experiencing PONV with age p = 0.288, gender p = 0.997, motion sickness p = 0.443, smoking history p = 0.958. Relationship of intraoperative risk factors for PONV with type of surgery p = 1,000, duration of surgery p = 0,978. The relationship between postoperative risk factors for experiencing PONV with opioid use p = 1,000, pain degree p = 1,000. Most general anesthesia patients were aged 26-35 years, most gender was female, most motion history was no history, most smoking history ie no history, the most type of surgery is oncology, the most duration is 60 minutes, the most opioid use is using, the highest degree of pain is mild.